DESCRIPTION OF THE USE OF ANTIBIOTICS WITH PRESCRIPTION AND WITHOUT DOCTOR'S PRESCRIPTION IN ESTER FARMA PHARMACY DELI SERDANG DISTRICT - Dilla Sastia Mara; Muharti Sanjaya (PT. Radja Intercontinental Publishing, 2022)
Antibiotics are drugs derived from all or certain parts of microorganisms and are used to treat bacterial infections. Antibiotics have long been used to fight diseases caused by bacterial infections. The irrational use of antibiotics will cause resistance problems. Resistance problems due to irrational use of antibiotics, one of which is caused by use that is not in accordance with the patient's condition, which can occur due to the use of antibiotics without a doctor's prescription. The use of antibiotics without a doctor's prescription can potentially pose various risks, including an increase in the number of cases of infection caused by resistant pathogenic bacteria, an increase in the risk of adverse drug events. decrease in the effectiveness of therapy and increase in health costs. This research is a descriptive study with cluster random sampling. The study was conducted prospectively to determine the use of antibiotics without a doctor's prescription and retrospectively to determine the use of antibiotics with a doctor's prescription. The research was conducted in August 2019 at the Laju Farma Pharmacy, Deli Serdang Regency. The results showed that the use of antibiotics with a doctor's prescription at the Laju Farma Pharmacy, Deli Serdang Regency during August 2019 was 90 prescriptions (15.95%) out of 564 prescriptions, patients who used antibiotics without doctor's prescriptions for 72 patients (10.74%) and 670 patients.